Negative Politeness Strategies in “How To Train Your Dragon: Homecoming” Movie - Ramadhan, Muhammad Rayhan; Afriana, Afriana (Prosiding, 2024)
This research aimed to discover the negative politeness strategies in “How To Train Your Dragon: Homecoming” movie. In this research, qualitative descriptive used as the research method. The researchers used the transcript of “How To Train Your Dragon: Homecoming” as the data source. In collecting the data, the method was observation and the technique was non-participant. Meanwhile, in analyzing the data, the method was identification and the technique was competence in comparing. The utterances from the transcript of the movie which were taken as the data were analyzed narratively. The researchers used the theory of (Brown & Levinson, 1987) to discover the negative politeness strategies. The researchers discovered 15 data of negative politeness strategies in the transcript of the movie that show be conventionally indirect; question, hedge; be pessimistic; minimize the imposition; give deference; and apologize, impersonalize S and H, state the FTA as a general rule and nominalize.